Short Fiber Reinforced Composite: a New Alternative for Direct Onlay Restorations - Sufyan Garoushi; Enas Mangoush; Pekka Vallittu; Lippo Lassila (Netherlands, 2022)
OBJECTIVES:
To determine the static load-bearing capacity of direct composite onlay restorations made of novel filling composite resin system which combines short fiber-reinforced composite resin (FC) and conventional particulate filler composite resin (PFC).
METHODS:
Three groups of onlay restorations were fabricated (n = 8/group); Group A: made from conventional particulate filler composite resin (Z250, 3M-ESPE, USA, control), Group B: made from short fiber-reinforced composite resin (EverX posterior, StickTeck Ltd, member of GC group, Turku, Finland) as substructure with 1 mm surface layer of PFC, Group C: made from FC composite resin. The specimens were incrementally polymerized with a hand-light curing unit for 80 s before they were statically loaded with two different sizes (3 & 6 mm) of steel ball until fracture. Failure modes were visually examined. Data were analyzed using ANOVA (p = 0.05).
RESULTS:
ANOVA revealed that onlay restorations made from FC composite resin had statistically significantly higher load-bearing capacity (1733 N) ( p < 0.05) than the control PFC composite resin (1081 N). Onlays made of FC composite resin with a surface layer of PFC gave force values of 1405 N which was statistically higher than control group ( p < 0.05). No statistically significant difference was found in the load-bearing capacity between groups loaded by different ball sizes.
SIGNIFICANCE:
Onlay restorations combining base of short fiber reinforced composite resin as substructure and surface layer of conventional composite resin displayed promising performance in high load bearing areas.